Streaming of medical images using JPEG2000 Interactive Protocol. (1st January 2012) - Pambrun, Jean-François; Noumeir, Rita
Access to all relevant information at the diagnostic decision moment improves the quality of care. With the deployment of the electronic health records (EHRs), information now exits in multiple distributed systems. When conducting diagnosis based on medical images, physicians often need to compare current images with older ones that may need to be imported prior to visualisation. This leads to persistency management and information consistency issues. JPEG2000 Interactive Protocol (JPIP) can be used to avoid imports by streaming images and significantly reduce bandwidth requirements. In this paper, we describe how JPIP can enable two interactive visualisation schemes, 'zoom and pan' and a magnification lens, to significantly improve user experience and productivity while minimising network usage. We will show that, with carefully selected compression parameters, JPIP allows physicians to start their investigation within few seconds of the initial request and stay productive during the entire download process.